OPTIMASI KOMPOSISI TWEEN 80 DAN SPAN 80 SEBAGAI EMULGATOR DALAM REPELAN MINYAK ATSIRI DAUN SERE (Cymbopogon citratus (DC) Stapf) TERHADAP NYAMUK Aedes aegypti BETINA PADA BASIS VANISHING CREAM DENGAN METODE SIMPLEX LATTICE DESIGN - Endah Nurlaela; Nining Sugihartini; Azis Ikhsanudin (Universitas Ahmad Dahlan, 2012)
The disease of Dengue hemorrhagic fever (DHF) is caused by the bite of female Aedes aegypti mosquito. Cream of repelan sere leaf essential oils can be used to prevent mosquito bites. The cream of volatile oil sere (Cymbopogon citratus (DC) Stapf) required emulsifier to maintain the stability of cream. Tween 80 and Span 80 is a widely used emulsifier in a cream formula. Aims of this study is to determine the optimum composition of Tween 80 and Span 80 as emulsifier in a cream repelan of sere leaf essential oils in the basis Vanishing Cream with Simplex Lattice Design methode. Three Formula cream is designed based on the Simplex Lattice Design methode with a ratio of Tween 80: Span 80 as follows: FI (100%-0%), F II (50%-50%), F III (0%-100%). Cream was then tested repelan activity and physical properties that include spreadibility, adhesivity and irritation. Data of physical properties and repellant activity was calculate to get the optimum formula. The validity of optimization methods was evaluated by comparing experimental results with predicted results in optimum cream formula with t test at 95% level of confidence. The results of study showed that the optimum composition of Tween 80: Span 80 was 60%:40%. Cream with optimum emulsifier composition was predicted has spreadibility 29.24 cm2; adhesivity 3.512 seconds; irritation 0.608; power repelan 41.469 minutes. T test results showed no significant differences between the experimental results and predicted results (p <0.05).